The Utilization of Virtual Learning Environment in Malaysian Non-Arabic Speaking Learners’ Classroom - Noorafini Kassim; Muhammad Sabri Sahrir (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study aimed to understand the utilization of VLE in Non-Arabic Speaking Learners’ classrooms from the perspective of Arabic teachers in higher education institutions. Purposive sampling was utilized to pick the research sample for this study. Then, the sample used for this study consisted of 3 Arabic language teachers. One-to-one in-depth interviews were conducted with the three informants. Semi-structured interviews were used to gather the data to allow the informants to express their experiences in an accessible manner. A case study was used in this study to create a qualitative design. The researcher used a method called thematic analysis (TA) and followed a few steps, including (i) word-by-word transcription, (ii) interview transcription, (iii) coding, and (iv) labeling. The findings illustrated the Arabic teachers’ perspectives on using VLE, the approaches when implementing VLE, and how VLE can effectively teach the Arabic language. The responses of the three informants would illustrate the main themes found using the thematic analysis (TA) method. The analysis of this study helps provide such information to universities on the perspectives of Arabic teachers on the use of VLE, their approaches when implementing VLE, and how VLE can be effective in their language teaching in a virtual learning context. This study allows us to understand better how Malaysian Arabic teachers adapt to virtual language learning environments by utilizing VLE at the university level.